2002
DOI: 10.1021/ie010303h
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Atomistic Simulations and Experimental Measurements of Light Gas Permeation through Zeolite Membranes

Abstract: We present experimental and theoretical results for single-component permeance of CH 4 and CF 4 through a supported silicalite membrane at a range of temperatures and pressures. Our theoretical model uses a continuum description of molecular transport through zeolite crystals that is directly parametrized from atomically detailed simulations of molecular adsorption and transport. This approach does not require any assumptions regarding the loading dependence of the adsorbed species' transport or Maxwell-Stefan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 59 publications
(205 reference statements)
8
66
0
Order By: Relevance
“…For higher pressures the adsorption isotherm for CH 4 in Figure 1 slightly underestimates the experimental values, while the CF 4 loading is overestimated relative to experiments. 21,36 The calculated isotherms for Ar slightly overestimate the experimental values at low pressures, while the isosteric heats of adsorption are slightly underestimated. 37 For SF 6 the loading is underestimated relative to experiments at low pressures while the isosteric heats of adsorption are overestimated.…”
Section: Details Of Model and Calculationsmentioning
confidence: 88%
See 1 more Smart Citation
“…For higher pressures the adsorption isotherm for CH 4 in Figure 1 slightly underestimates the experimental values, while the CF 4 loading is overestimated relative to experiments. 21,36 The calculated isotherms for Ar slightly overestimate the experimental values at low pressures, while the isosteric heats of adsorption are slightly underestimated. 37 For SF 6 the loading is underestimated relative to experiments at low pressures while the isosteric heats of adsorption are overestimated.…”
Section: Details Of Model and Calculationsmentioning
confidence: 88%
“…To determine E ads , we computed the orientationally averaged D(0) for CF 4 , SF 6 , and CH 4 at 298, 373, and 473 K, then fitted these results to the usual Arrhenius form. This gives the apparent activation energy for self diffusion of an isolated adsorbate as 4.25 kJ/mol for CH 4 , 36 4.43 kJ/mol for CF 4 , and 7.44 kJ/mol for SF 6 . The ratio aa /E ads is therefore 3.5, 4.0, and 4.0 for CH 4 , CF 4 , and SF 6 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that atomically detailed calculations can be used to quantitatively predict the single‐component flux of light gases such as CH 4 and CF 4 through zeolite membranes 14. In our approach, atomistic simulations are used to determine the adsorption isotherms and loading‐dependent Fickian diffusion coefficient, D t ( c ).…”
Section: Introductionmentioning
confidence: 99%
“…The infinite-dilution activation energies for methane diffusion in the two pairs of IRMOFs shown in Figure 2(b) and (c) were calculated by performing MD simulations at three temperatures: T ¼ 200, 300 and 400 K. The values obtained are 8.29 and 9.65 kJ/mol for IRMOF-11 and IRMOF-13, respectively, which are much larger than that in their corresponding non-catenated counterparts with the values of 4.89 and 4.90 kJ/mol for IRMOF-12 and IRMOF-14, respectively. The infinite-dilution activation energy of CH 4 in silicalite is found experimentally to be 5.7 kJ/mol [47] and the simulated result is 4.4 kJ/mol [48]. Therefore, the activation energy in the non-catenated IRMOFs is similar to that in silica zeolites, while it is greatly increased in its corresponding catenated IRMOFs, causing a much lower diffusivity in them.…”
Section: Effect Of Catenation On Methane Diffusivity In Irmofsmentioning
confidence: 75%